Integrating Sustainability, Digital Transformation and State Policy Post 2024 - Nurmi Nurmi; Muchriana Muchran (CV. AFDIFAL MAJU BERKAH, 2025)
This study examines the latest phenomena in capital budgeting in Indonesia, characterized by the integration of sustainability principles (Environmental, Social, and Governance/ESG) and the utilization of digital technology in investment decision-making processes. This transformation marks a paradigm shift from the traditional approach focused solely on financial efficiency to a more holistic strategic approach that incorporates social, environmental, and corporate governance aspects. The study also explores the role of government policies and technological advancements in supporting the implementation of adaptive and transparent capital budgeting. The findings reveal that although challenges in adopting technology and ESG remain significant, especially among small and medium enterprises, companies that successfully integrate these aspects demonstrate greater resilience and competitive advantage. The research emphasizes the importance of collaboration among the private sector, government, and academia to accelerate the transformation of capital budgeting towards a more inclusive and sustainable economic development in Indonesia.